Financial Incentives for Whistleblowers in European Capital Markets Law - Fleischer, Holger; Schmolke, Klaus Ulrich (European Company Law, 2012)
The European Commission has recently released a Proposal for a Regulation on market abuse, to increase investor confidence and market integrity in European capital markets law. One of its most innovative elements involves allowing Member States to provide financial incentives to whistleblowers who report cases of market abuse. In this, the Commission has apparently taken inspiration from the US legislation which with the Dodd Frank Act of 2010, significantly expanded its whistleblower reward program. This article examines both the US and the European regulations, and evaluates the advantages and disadvantages of offering financial incentives to encourage informants to blow the whistle. Finally, it looks at the potential structure of a reward program, examining the balance required between external rewards and internal company compliance processes.
Keywords: Whistleblower; whistleblowing; financial incentives; finanzielle Anreize; Dodd Frank Act; informants; Compliance